FATIGUE STRENGTH ANALYSIS AND OPTIMIZATION OF FSC RACING EXHAUST SYSTEM - QI Qi; LIU HaoTian; WU XiaoJian; LUO Cheng (Jixie qiangdu)
The exhaust pipe of engine is subjected to alternating load of low and high temperatures during operation,which is prone to fatigue damage.For the FSC（Formula Student China） racing engine with the highest speed of 11 000 r/min～13 OOOr/min,the exhaust pipe fatigue problem is more serious.In this paper,the FSC racing exhaust system is taken as the research object to analyze its fatigue strength and optimize the exhaust pipe thickness.Firstly,the Fluent software is used to analyze the conjugate heat transfer of the exhaust system to determine the temperature distribution of the exhaust system.Then the temperature distribution is mapped to the finite element mesh of the exhaust system,and the thermal stress and thermal strain are analyzed by finite element technology.Subsequently,two schemes including exhaust manifold " normal operation-parking cooling" cycle and extreme working condition cycle are designed to carry out the thermal cycle simulation.It is found that the exhaust gas accumulates plastic deformation under the alternating load of each cycle,and the exhaust system will eventually crack and be destroyed.Finally,the fatigue life of the two schemes is studied by using Ansys nCode DesignLife fatigue analysis software.The results show that both schemes effectively reflect the life expectancy of low-cycle fatigue damages under the combined action of exhaust manifold temperature field,thermal stress and strain.Based on the above analysis,the exhaust thickness is optimized by the extreme working condition circulation scheme.and it is verified by experiments that the 1.2 mm thickness steel pipe meets the FSC exhaust requirements.